2022
DOI: 10.1186/s13102-022-00499-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Such a massive part of rehab is between the ears’; barriers to and facilitators of anterior cruciate ligament reconstruction rehabilitation: a qualitative focus group analysis

Abstract: Background Current evidence demonstrates that few patients complete anterior cruciate ligament reconstruction rehabilitation according to evidence-based guidelines. It is important to investigate the viewpoints of our patients to identify patient-reported barriers and facilitators of anterior cruciate ligament reconstruction rehabilitation. Qualitative analysis can provide insight into potential methods for improving the delivery of rehabilitation services. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Multiple factors likely contribute to patients receiving a low dosage of physiotherapy treatment following ACLR, including low motivation to complete rehabilitation (Thorstensson et al, 2009), a lack of patient education regarding post-ACLR rehabilitation (Cailliez et al, 2012), or a lack of surgeon endorsement of rehabilitation (Ebert et al, 2019b). Patients also report frustration and disappointment with a physiotherapist's ability to manage late-stage ACLR rehabilitation (Walker et al, 2022), which could lead to patients prematurely disengaging in physiotherapy, resulting in a low number of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors likely contribute to patients receiving a low dosage of physiotherapy treatment following ACLR, including low motivation to complete rehabilitation (Thorstensson et al, 2009), a lack of patient education regarding post-ACLR rehabilitation (Cailliez et al, 2012), or a lack of surgeon endorsement of rehabilitation (Ebert et al, 2019b). Patients also report frustration and disappointment with a physiotherapist's ability to manage late-stage ACLR rehabilitation (Walker et al, 2022), which could lead to patients prematurely disengaging in physiotherapy, resulting in a low number of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…If this leads to changes in confidence, self-efficacy, goals, kinesiophobia, or mental status, it is likely to affect recovery progression. 5,23,68,74 Numerous studies agree psychosocial factors such as emotion often intertwine with decision-making and influence future outcomes.…”
Section: Impact Of Injury Experiencementioning
confidence: 99%
“…Patients' descriptions of feelings include: burden, worry, frustration, hopelessness, devastation, and isolation. 23,30,36,52,68 Mental health conditions, such as anxiety and depression, may increase in severity in response to injury and be detrimental to outcomes. 46 Schaffer et al 58 observed outcomes of patients stratified into 3 cohorts: clinical diagnosis of depression, situational depression, and no depression.…”
Section: Impact Of Injury Experiencementioning
confidence: 99%
“…Thus, the rehabilitation setting seems to influence the rehabilitation process more than expected. 6 More than 5 years after their ACL-R, patients either experience symptom resolution or feel forced to accept the negative aspects of necessary lifestyle changes as a result from the ACL injury. 7 Regardless of treatment, rehabilitation after ACL injury is typically considered long and demanding, including both physical and psychological challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that affected rehabilitation as expressed by patients were the rehabilitation characteristics, service delivery by the physical therapist, physiological and psychological factors, and interaction with others. Thus, the rehabilitation setting seems to influence the rehabilitation process more than expected 6 . More than 5 years after their ACL‐R, patients either experience symptom resolution or feel forced to accept the negative aspects of necessary lifestyle changes as a result from the ACL injury 7 .…”
Section: Introductionmentioning
confidence: 99%